Assessing degradation of power transformer solid insulation considering thermal stress and moisture variation - Medina, Ricardo Daniel (2017)
This paper presents a novel method for estimating the degradation of solid insulation in power transformers, considering thermal ageing and paper moisture dynamics. Current ageing models are based on both, experimental evidence and theoretical developments; considering that all models are approximation to reality, loss of life estimation could be found in a large range depending on the evidence considered; this amplitude could lead inaccurate results to make adequate decisions in an asset-management context. These differences in results can be explained because the models consider only nominal operative temperatures ranges overlooking low and high temperatures degradation process and the influence of variations in paper moisture content. Considering the above, this document proposes a holistic methodology for solid insulation ageing assessing based on all thermal degradation process (oxidation, hydrolysis and pyrolysis) and the influence of dynamics on paper moisture. Paper moisture is estimated using as input external variables such as: load, ambient temperature, transformer technical data and measurements regarding oil moisture, in order to consider uncertain in oil moisture growing Arithmetic-Brownian-Motion algorithms are presented. The proposed methodology was tested for four power transformers, for which load and ambient temperature hourly profiles are available over a period of almost nine years. In order to compare different degradation rates, three alternatives to model the chemical environment in which cellulose is aged, are analysed. Results are presented, and conclusions are finally detailed.